Extending our understanding of the social determinants of physical activity and sedentary behaviors in families: a systems mapping approach - Rhodes, Ryan E.; Banik, Anna; Szczuka, Zofia; Aulbach, Matthias Burkard; DeSmet, Ann; Durand, Hannah; Gatting, Lauren; Green, James; Hillison, Emily Zelda; Masaryk, Radomír; Radtke, Theda; Rigby, Benjamin P.; et al. (Journal of physical activity and health, 2025)
Background: The social environment is important to consider for effective promotion of movement behaviors like increased physical activity (PA) and reduced sedentary behavior (SB); yet, it is less often considered than individual and built environments. One way to advance social environment research is to develop system maps, an innovative, participatory, action-oriented research process that actively engages stakeholders to visualize system structures and explore how systems “work.” The purpose of this research was to develop PA and SB system maps of the social environment embedded within the core/nuclear family system. Methods: The development process began with a 2-day multicountry, 16-researcher, in-person participatory workshop in August 2023, followed by multiple online follow-up consultations. Attendees contributed to the creation of the maps through shared development of critical determinants and their causal pathways. The structure of the final maps was analyzed using network analysis methods to identify indicators of centrality, and key feedback loops and areas for potential intervention were explored. Results: Key central determinants that were likely critical targets for systems intervention to produce changes in PA and SB and featured prominently in most of the reinforcing and balancing feedback loops included shared family interests, values and priorities, family logistical support, family cohesion/organization, and shared experiences. The maps also highlighted key determinants of the broader social environment external to the family. Conclusions: These system maps support current evidence on movement behaviors in family systems and socioecological theories and have the utility to galvanize future research and policy to promote PA and reduce SB.